CGIAR Research Program Portfolio report 2016 - CGIAR System Organization (CGIAR System Organization, 2017)
This sixth annual CGIAR Research Program Portfolio Report (2016 Portfolio Report) provides a synthesis and analysis of progress and achievements by the portfolio of 15 CGIAR Research Programs (CRPs) in 2016, together with reporting on management of CGIAR's Crop Collections – the Genebanks – in Appendix 1. Taking note that CGIAR has adopted a new Strategy and Results Framework to frame its strategic research agenda from 2017, the material presented represents the final year of reporting against CGIAR’s 2010 Strategy and Results Framework1 , which prioritized four system level outcomes (SLOs): Reducing rural poverty; Improving food security; Improving nutrition and health; Sustainable management of natural resources.